Partisan identities and interpretations of economic data. (8th August 2022) - Doherty, David; Hansen, Kathryn
ABSTRACT: We report findings from three survey experiments that assess how partisanship affects people's subjective and objective interpretations of factual economic data. Partisan biases substantially affect how people subjectively rate economic performance. However, we find only scattered, inconclusive evidence that these biases affect objective understanding of factual data. Our experiments also offer preliminary evidence regarding how these biases might be attenuated. In the first two experiments, we assess whether reducing the amount of volatility in the graphs we present to respondents attenuates the partisan biases we identify; in the third we assess whether attributing the data to an ideologically-friendly – or unfriendly – media source affects these biases.